Ibn al-Faqih al-Hamdhani and his book Countries - Critical Study - (Journal of the College of Basic Education, 2022)
IBN AL- faqih Al- Hamadani and his book Al- Buldan This paper intends to shed alight on Ahmed b. Muhammad b.Ishaq b. Ibraheem (Ibn Al-faqih) died on 340 H/951A.D. Who was one of the muslums geographers and is still unstudied well by scholars . Nevertheless , this paper dealt with those aspects are unknown to historians and geographers, particularly his historical writings and narrations, his metholodology, in addition to those views on the original text of his book. We have to say that the copies the " short book " of Al- Buldan and the book of Al- Buldan itself, now in use, are not the original manuscript of the book.